Impacts of Topsoil and Surface Water Salinity on Agriculture: A Study at Paikgachha, Khulna (The Dhaka University Journal of Earth and Environmental Sciences, 2021)
Studying the structure, intensity and track of tropical cyclone is very important in effective tropical cyclone warning. In this study, an attempt has been made to simulate the Super Cyclone Amphan to reproduce the structure, intensity and track of the storm that occurred over the Bay of Bengal and made landfall over the coastal zone of Sundarban between Western Bangladesh and Eastern West Bengal of India on 20 May 2020. The Weather Research and Forecasting (WRF) Model was run 120 hours from 0000 UTC of 16 May to 0000 UTC of 21 May 2021 with 9 km horizontal resolution to simulate the selected storm. The model simulated intensity and track of the storm were compared with that of best track data of India Meteorological Department (IMD). The results obtained from the WRF model indicated that the intensity of the selected cyclone in terms of Mean Sea Level Pressure (MSLP) and Maximum Sustained Wind speed (MSW) were 905 hPa and 243 kph whereas the observed MSLP and MSW were close to 920 hPa and 241 kph respectively. It was also indicated that the model predicted the track of the cyclone reasonably well and it was quite close to the best track data throughout its path till landfall with very small deviation and the cyclone made landfall at 7-8 hours before the actual landfall with 167.4 km position error.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 8(2), 2019, P 25-32